Caregiver anxiety and the association with acute postoperative pain in children undergoing elective ambulatory surgery in a lower‐middle‐income country setting. Issue 9 (9th July 2020) - Knoetze, Reynard; Lachman, Anusha; Moxley, Karis; Chetty, Sean
Abstract: Background and aims: Moderate to severe postoperative pain complicates surgeries performed on children in upper‐income countries. The successful management of postoperative pain in children requires a biopsychosocial approach. Situational anxiety and anxiety disorders among caregivers influence a child's perioperative experience. This study aims to determine whether there is an association between caregiver's preoperative anxiety and children's postoperative pain in a lower‐middle‐income country (LMIC) setting. Methods: In this cross‐sectional, descriptive study, we recruited 76 children aged 4‐12 years, undergoing elective ambulatory tonsillectomy or adenotonsillectomy. Primary caregivers completed validated measures of anxiety (the Beck Anxiety Inventory [BAI] and the Kessler Psychological Distress Scale [K10]) prior to the children undergoing surgery. Postoperative pain was measured using the Wong‐Baker Faces Pain Rating Scale 4 hours after surgery. Results: Caregiver anxiety was found in 31.7% of participants using the K10 and in 42.1% using the BAI. Moderate to severe postoperative pain was reported by 51% of children. There was a statistically significant correlation of moderate strength between anxiety scores of caregivers and children's self‐reported postoperative pain scores ( r = .47 for K10, r = .44 for BAI, P < .001 for both). Two median quantile regression models confirmed that K10 was positively associated with caregiver anxiety (WBFS) with slope = 0.16 and pseudo R 2 = 0.25 ( P = .002, 95CI: 0.06‐0.26) as was BAI with slope = 0.12 and pseudo R 2 = 0.22 ( P = .013 95CI: 0.03‐0.22). Conclusions: This study showed that preoperative caregiver anxiety is significantly associated with postoperative pain in children undergoing elective, ambulatory surgery in a LMIC setting (correlation of moderate strength). Interventions aimed at reducing caregiver anxiety should become an important component of the biopsychosocial management of postoperative pain in children.